DIATOM ASSEMBLAGES IN THE UPPER LAYER OF BOTTOM DEPOSITS: DISTRIBUTION OVER MORPHOSTRUCTURAL SHELF ZONES OF THE NORTH-WESTERN ANTARCTIC PENINSULA - Ogienko, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This paper presents the results of research into marine diatom assemblages in surface shelf deposits of the North-Western Antarctic Peninsula area. Five clusters of diatom assemblages have been identified, according to their taxonomic composition, ecological structure, and distribution in different morphostructural shelf zones. We have considered the factors that affect the assemblage composition and distribution. In the study area, the dominant diatom species are the antarctic marine planktonic and cryophilic ones, their number increasing considerably in the inner shelf zone due to a natural barrier of big islands. The share of oceanic subantarctic species grows toward the open ocean (in the external shelf). The number of semibenthic and benthic diatoms is substantially larger in the shallow near island waters. The originality of the investigation is in identifying regular patterns in the diatom taxonomy and ecology depending on their distribution in the surface deposits associated with different morphostructural shelf zones of the North-Western Antarctic Peninsula. The new data on the diatoms may be of use in backstripping analysis of the Antarctic area.
Keywords: diatoms; marine bottom deposits; morphostructural shelf zones; Antarctic Peninsula